Does the Interpersonal Model Generalize to Obesity Without Binge Eating?. (7th July 2016) - Lo Coco, Gianluca; Sutton, Rachel; Tasca, Giorgio A.; Salerno, Laura; Oieni, Veronica; Compare, Angelo
Abstract: The interpersonal model has been validated for binge eating disorder (BED), but it is not yet known if the model applies to individuals who are obese but who do not binge eat. The goal of this study was to compare the validity of the interpersonal model in those with BED versus those with obesity, and normal weight samples. Data from a sample of 93 treatment‐seeking women diagnosed with BED, 186 women who were obese without BED, and 100 controls who were normal weight were examined for indirect effects of interpersonal problems on binge eating psychopathology mediated through negative affect. Findings demonstrated the mediating role of negative affect for those with BED and those who were obese without BED. Testing a reverse model suggested that the interpersonal model is specific for BED but that this model may not be specific for those without BED. This is the first study to find support for the interpersonal model in a sample of women with obesity but who do not binge. However, negative affect likely plays a more complex role in determining overeating in those with obesity but who do not binge. Copyright © 2016 John Wiley & Sons, Ltd and Eating Disorders Association.